GAMBARAN PENGETAHUAN KELUARGA DENGAN HIPERTENSI TENTANG PERAWATAN MANDIRI HIPERTENSI PADA MASA PANDEMI COVID-19 - ni kadek sutini; Kadek Ayu Ananda Maharini; Ni Wayan Sukma Antari; I Gede Putu Darma Suyasa (JURNAL MEDIKA USADA, 2022)
Background: People with hypertension are a vulnerable group to morbidity and mortality, especially during the Covid-19 pandemic. During the period of social restrictions, self-management of hypertension is recommended for patients especially in controlling their blood pressures. Families play an important role in the self-management carried out by the patient at home. Purpose: This study aimed to identify knowledge of families with hypertension about the self-management of hypertension. Methods: This study employed a descriptive design with a cross-sectional approach. The research was carried out in Serangan Village, South Denpasar District for 1 month. This study involved 145 families with hypertension. Data was collected using questionnaires. The data wqs analyzed univariately using SPSS version 20. Results: showed that most families had adequate knowledge of hypertension self-management (66.2%). However, the remaining 33.8% indicated poor knowledge on self-management. Based on the six components of hypertension self-management, most families in this study had adequate knowledge on diet management (66.2%), physical activity management (67.6%), stress management (89.0%), alcohol intake management (53.8%), smoking habit management (85.5%) and medication adherence (92.4%). Conclusion: Health care workers are suggested to strengthen family education about hypertension self-management especially those indicating poor knowledge via home visits with Pandemic protocols.